2014
DOI: 10.1002/2014wr015388
|View full text |Cite
|
Sign up to set email alerts
|

Micromodel study of two‐phase flow under transient conditions: Quantifying effects of specific interfacial area

Abstract: Recent computational studies of two-phase flow suggest that the role of fluid-fluid interfaces should be explicitly included in the capillarity equation as well as equations of motion of phases. The aim of this study has been to perform experiments where transient movement of interfaces can be monitored and to determine interfacial variables and quantities under transient conditions. We have performed two-phase flow experiments in a transparent micromodel. Specific interfacial area is defined, and calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 45 publications
2
73
0
Order By: Relevance
“…In such cases, the dominance of viscous forces over capillary forces (high values of Ca) favors generation of large blobs by viscous fingering. By exceeding a threshold value of Ca, viscous forces of the invading fluid flowing alongside the blobs tend to mobilize or fragment the residual oil into small parts [ Ng and Payatakes , ; Chatzis and Morrow , ; Koplik and Lasseter , ; Dias and Payatakes , ; Hinkley et al ., ; Joekar‐Niasar and Hassanizadeh , 2012a, 2012b; Karadimitriou et al ., ] reducing the size of the trapped blobs as illustrated in Figure . These results are in good agreement with the stochastic simulation of the motion, breakup, and stranding of oil ganglia carried out by Ng and Payatakes [], which concluded that mobilized solitary ganglia are destined to either get stranded whole (intermediate values of Ca) or to break up in daughter small ganglia which subsequently get stranded (high values of Ca) [ Weinhardt and Heinemann , ].…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, the dominance of viscous forces over capillary forces (high values of Ca) favors generation of large blobs by viscous fingering. By exceeding a threshold value of Ca, viscous forces of the invading fluid flowing alongside the blobs tend to mobilize or fragment the residual oil into small parts [ Ng and Payatakes , ; Chatzis and Morrow , ; Koplik and Lasseter , ; Dias and Payatakes , ; Hinkley et al ., ; Joekar‐Niasar and Hassanizadeh , 2012a, 2012b; Karadimitriou et al ., ] reducing the size of the trapped blobs as illustrated in Figure . These results are in good agreement with the stochastic simulation of the motion, breakup, and stranding of oil ganglia carried out by Ng and Payatakes [], which concluded that mobilized solitary ganglia are destined to either get stranded whole (intermediate values of Ca) or to break up in daughter small ganglia which subsequently get stranded (high values of Ca) [ Weinhardt and Heinemann , ].…”
Section: Resultsmentioning
confidence: 99%
“…Projection of this surface onto the p c – S w plane would form the hysteresis loop of the primary (or main) drainage and imbibition curves. Several experimental and modeling studies have suggested that the saturation–capillary pressure interfacial area surface is indeed unique for all drainage and imbibition equilibrium points, whether on the main or on scanning curves (e.g., Held and Celia, 2001; Chen and Kibbey, 2006; Chen et al, 2007; Joekar‐Niasar et al, 2008; Joekar‐Niasar and Hassanizadeh, 2011, 2012; Karadimitriou et al, 2014).…”
Section: Numerical Modelsmentioning
confidence: 99%
“…Simplified approaches that allow experimental visualization of the flow involve the use of so‐called micromodels. In these micromodels, idealized 2‐D porous media facilitate optical access and thus simultaneous observation of the flow in multiple phases [ Zhang et al ., ; Armstrong and Berg , ; Karadimitriou et al ., , among others]. More recently, a number of studies have reported measurements in such micromodels using advanced optical diagnostic techniques (e.g., micro‐PIV) to capture spatially and temporally resolved velocity data of immiscible multiphase flow [ Blois et al ., ; Kazemifar et al ., ; Kazemifar et al ., ; Roman et al ., ].…”
Section: Introductionmentioning
confidence: 99%